Measuring the aggregation of CHO cells prior to single cell cloning allows a more accurate determination of the probability of clonality. (17th June 2017) - Klottrup, Kerensa J.; Miro‐Quesada, Guillermo; Flack, Layla; Pereda, Ivan; Hawley‐Nelson, Pamela
Abstract : The manufacturing process for biotherapeutics is closely regulated by the Food and Drug Administration (FDA), European Medicines Agency (EMA) and other regulatory agencies worldwide. To ensure consistency of the product of a manufacturing cell line, International Committee on Harmonization guidelines (Q5D, 1997) state that the cell substrate should be derived from a single cell progenitor, i.e., clonal.Cell lines in suspension culture may naturally revert to cell adhesion in the form of doublets, triplets and higher order structures of clustered cells. We can show evidence of a single colony from limiting dilution cloning or in semi‐solid media, but we cannot determine the number of cells from which the colony originated. To address this, we have used the ViCELL® XR (Beckman Coulter, High Wycombe, UK) cell viability analyzer to determine the proportion of clusters of two or more cells in a sample of the cell suspension immediately prior to cloning. Here, we show data to define the accuracy of the ViCELL for characterizing a cell suspension and summarize the statistical model combining two or more rounds of cloning to derive the probability of clonality. The resulting statistical model is applied to cloning in semi‐solid medium, but could equally be applied to a limiting dilution cloning process. We also describe approaches to reduce cell clusters to generate a cell line with a high probability of clonality from a CHO host lineage. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 34:593–601, 2018